2017
DOI: 10.1101/193672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation of phosphate solubilizingPseudomonasstrains from apple rhizosphere in the Trans Himalayan region of Himachal Pradesh, India

Abstract: Total fifteen phosphate solubilizing bacteria were isolated from rhizosphere soil of apple tree on Kings' B medium belonging to genus Pseudomonas spp. They were characterized on the basis of morphological and biochemical characteristics. Preliminary selection as phosphate solubilizing bacteria were done on the basis of formation of transparent zone around the colony on Pikovskaya's agar medium containing 0.5% triclcium phosphate (TCP).Maximum in vitro phosphate solubilization on Pikovskaya's agar plates after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Phosphorus and potassium fertilizers are not effectively used at low soil pH. Sharma et al (2017) studied the bacteria of the genus Pseudomonas inhabiting the roots of apple trees in terms of their ability to dissolve insoluble phosphorus compounds. They believe that organic compounds secreted by apple roots can stimulate the multiplication of phosphorolytic (fluorescing) Pseudomonas bacteria and Bacillus bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus and potassium fertilizers are not effectively used at low soil pH. Sharma et al (2017) studied the bacteria of the genus Pseudomonas inhabiting the roots of apple trees in terms of their ability to dissolve insoluble phosphorus compounds. They believe that organic compounds secreted by apple roots can stimulate the multiplication of phosphorolytic (fluorescing) Pseudomonas bacteria and Bacillus bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous PSB bacteria were previously identified as members of genus Pseudomonas with plant growth promoting ability. For instance, the phosphate solubilizing ability of a P. aeruginosa strain was reported by Sharma et al, and was reckoned as a potential phosphate solubilizer and biofertilizer in apple crops [ 76 ]. Additionally, endophytic PSB Pseudomonas fluorescens isolates were shown to stimulate the growth of Pisum sativum L. plants [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paul and Sinha (2017) found that Pseudomonas strain KUPSB12 demonstrated an effective phosphate solubilization index of 2.85 on Pikovskya agar plates, along with a very high production of soluble phosphate (219±0.33 µg ml -1 ) in a liquid medium. Similarly, Sharma et al (2017) reported that potential phosphate solubilizing Pseudomonas aeruginosa strain An-Mg, isolated from the rhizosphere soil of apple trees, could serve as both a biofertilizer and a potential biocontrol agent. Kloepper et al (1988) highlighted phosphorus solubilization as the most readily available form for plant growth.…”
Section: Phosphate Solubilization Activity (Liquid Assay)mentioning
confidence: 98%